Performance of Cu‐Ce/M‐Al (M = Mg, Ni, Co, Zn) hydrotalcite derived catalysts for hydrogen production from methanol steam reforming. (2nd March 2021) - Qiao, Weijun; Yang, Shuqian; Zhang, Lei; Tian, Yuan; Wang, Honghao; Zhang, Caishun; Gao, Zhixian
Summary: M‐Al (M = Mg, Ni, Co, Zn) hydrotalcite was synthesized on the surface of the γ ‐Al2 O3 carrier, and hydrotalcite was calcined to corresponding carrier. Then, A series of Cu‐Ce/M‐Al catalysts were prepared by the sequential dip method. The catalysts were characterized by the means of XRD, BET, H2 ‐TPR, and XPS, which investigated the effects of different divalent metals M on the structure, properties, and catalytic performance of hydrotalcite derived catalysts for hydrogen production from methanol steam reforming. The main reasons for different effects on the performance of catalysts lie in the difference of the dispersion, reduction temperature, and the content of oxygen vacancies on the surface. Among them, Ce‐Cu/Zn‐Al catalyst had the best performance. When the reaction temperature was 250°C, the molar ratio of water to methanol was 1.2, and the space velocity of methanol gas was 800 hours −1, the methanol conversion reached 100%, and the H2 production rate was 779.7 STP cm 3  kg −1  s −1 . Abstract : The products of hydrogen combustion are environmentally friendly and pollution‐free to the current green chemical theme. Among Cu‐Ce/M‐Al (M = Zn, Ni, Mg, Co) catalysts, Ce‐Cu/Zn‐Al catalyst had the best performance for hydrogen production from methanol steam reforming. When the reaction temperature was 250°C, the molar ratio of water to methanol was 1.2, and the space velocity of methanol gas was 800 hours −1, the methanol conversion reached 100%, and H2 production rate was 779.7 STP cm 3 ·kg −1 ·s −1 .